Polyrostrata, a new genus of Sphaeropsidaceae from India - O.P.SINGH and C.UMA MAHESWARI, PRAMEELA DEVI T.*, NITA MATHUR, (Indian Phytopathology, 2009)
A new genus of Sphaeropsidacae, Polyrostrata is described from the the stems of Erianthus munja (Roxb.) Jesw. (Gramineae) in Delhi, India, producing the number of black fruiting bodies all over the stem.The new genus is characterized by the presence of thin, hyaline mycelium turned to thick walled, rough septate mycelium attached to the pycnidia as long, thick hairs; immersed and semi-immersed, irregular, black pycnidia having many number of beaks through which the spores are discharged in cirrus form; descrete, doliiform to ampulliform, hyaline and smooth conidiogenous cells with large globose guttulae and hyaline, aseptate, smooth, bacilliform conidia with several globose guttulae and slightly larger guttulae at each end. The type is P. indica sp. nov.